Pengaruh Brand Image, Harga, Atribut Produk, Ekuitas Merek, Promosi dan Kualitas Layanan terhadap Keputusan Pembelian Konsumen di Toko Metto Fashion Boyolali - A'yunin, Hanif, Zulfa Irawati, S.E., M.Si (2015)
This study aimed to analyze the influence of brand image, price, product attributes, Brand Equity, Promotion, Quality of Service of the Purchase Decision Metto Shop Fashion Boyolali. Population of this research is that people who are in the region of Surakarta. Samples used in this study were 100 respondents. The tools were used in this study include Test Validity, Test Rehabilitation, Normality Test and Classical Assumption Test, Multiple Regression, Coefficient of Determination Test, test F and test t. Test results of this study are not all the variables in this study individually (partial) have a significant influence on the purchase decision in Store Metto Fashion Boyolali. This can be seen in the significant variables t Brand Image, price, product attributes, Brand Equity, Promotion, Quality of Service of 0.000, 0.029, 0.015, 0.005, 0.036, and 0.019 less than 0.005. In the F test obtained F sig. 0,000 which is less than 0.05 then jointly variable Brand Image, price, product attributes, Brand Equity, Promotion, Quality of Service significantly to the purchase decision in Store Metto Fashion Boyolali. While the determination coefficient of 0.577 was obtained 57.7% of the variation means buying decision variables can be explained by the variable Brand Image, price, product attributes, Brand Equity, Promotion, Quality of Service while the remaining 42.3% explained by other factors outside the model examined